Calcium-dependent inactivation of calcium channels in cochlear hair cells of the chicken - Lee, Seunghwan (Blackwell Science Inc, 2007)
Voltage-gated calcium channels support both spontaneous and sound-evoked neurotransmitter release from ribbon synapses of cochlear hair cells. A variety of regulatory mechanisms must cooperate to ensure the appropriate level of activity in the restricted pool of synaptic calcium channels (∼100) available to each synaptic ribbon. One potential feedback mechanism, calcium-dependent inactivation (CDI) of voltage-gated, L-type calcium channels, can be modulated by calmodulin-like calcium-binding proteins. CDI of voltage-gated calcium current was studied in hair cells of the chicken's basilar papilla (analogous to the mammalian cochlea) after blocking the predominant potassium conductances. For inactivating currents produced by 2.5 s steps to the peak of the current–voltage relation (1 mm EGTA internal calcium buffer), single exponential fits yielded an average decay time constant of 1.92 ± 0.18 s (mean ±s.e.m., n = 12) at 20–22°C, while recovery occurred with a half-time of ∼10 s. Inactivation produced no change in reversal potential, arguing that the observed relaxation did not result from alternative processes such as calcium accumulation or activation of residual potassium currents. Substitution of external calcium with barium greatly reduced inactivation, while inhibition of endoplasmic calcium pumps with t-benzohydroquinone (BHQ) or thapsigargin made inactivation occur faster and to a greater extent. Raising external calcium 10-fold (from 2 to 20 mm) increased peak current 3-fold, but did not alter the extent or time course of CDI. However, increasing levels of internal calcium buffer consistently reduced the rate and extent of inactivation. With 1 mm EGTA buffering and in 2 mm external calcium, the available pool of calcium channels was half-inactivated near the resting membrane potential (−50 mV). CDI may be further regulated by calmodulin-like calcium-binding proteins (CaBPs). mRNAs for several CaBPs are expressed in chicken cochlear tissue, and antibodies to CaBP4 label hair cells, but not supporting cells, equivalent to the pattern seen in mammalian cochlea. Thus, molecular mechanisms that underlie CDI appeared to be conserved across vertebrate species, may provide a means to adjust calcium channel open probability, and could serve to maintain the set-point for spontaneous release from the ribbon synapse.